Effectiveness of anterior resection with total mesorectal excision in curative treatment for rectal carcinoma in males - Szynglarewicz, Bartłomiej; Matkowski, Rafał; Sydor, Daniel; Forgacz, Józef; Pudełko, Marek; Grzebieniak, Zygmunt (Contemporary Oncology/Współczesna Onkologia, 2007)
Aim: Aim of the study was to evaluate the effectiveness of anterior resection with total mesorectal excision (TME) in surgical management for rectal cancer in male patients, for whom the achievement of adequate radial resection margins may be more difficult than for females. Material and methods: Forty-three consecutive males with histologically confirmed carcinoma of the rectum operated on from 01.1998 to 12.1999 were studied prospectively. Patients underwent sphincter-preserving anterior resection of the rectum with TME. In Dukes stages B and C neo- or adjuvant therapy was administered: eight patients received preoperative irradiation and postoperative fluorouracil-based chemotherapy, fifteen received adjuvant chemoradiation. Results: Postoperative mortality was not noticed. In 4.6% of patients only local recurrence, in 18.6% only distant metastases and in 4.6% both failures occurred. Five-year overall survival was 71.5±9.8% (Kaplan-Meier). Survival was 100.0±0.0% for stage B, 60.0±13.1% for B and 25.0±16.4% for C (P<0.05, log-rank test). Lymph node involvement was a very important factor (P<0.001) of poor survival: N- vs N+, 82.9±6.5% vs 25.0±16.4%, respectively. For all node-positive patients with recurrent disease systemic dissemination was observed. Conclusions: TME technique results in low local recurrence rate and improved survival for male patients. It should be regarded as an integral aspect of the optimal surgical management for rectal cancer. Despite effective local control of TME and advantages of radio- and chemotherapy patients with lymph node metastases have poor prognosis.